PENGARUH KUALITAS, PERSEPSI NILAI, DAN CITRA TERHADAP KEPUASAN PENUMPANG BUS TRANSJOGJA - Petra Surya Mega Wijaya (Fakultas Bisnis UKDW, 2011)
The purpose of this study is to examine the effect of core quality, relational quality, perceived value, image towards TransJogja bus passenger’s satisfaction. A random sample of 100 was drawn from passengers in halt areas and another places. They have used TransJogja buses for at least three months. This study shows that core quality and relational quality have influence on the TransJogja bus passanger’s satisfaction, meanwhile perceived value and image have not influence on TransJogja bus passenger’s satisfactionKeywords: core quality, relational quality, perceived value, image, passenger’s satisfaction